Farmers knowledge, attitudes and practices (kap) in Embu and Taita benchmark sites before and after below-ground biodiversity project interventions - Mutsotso, B; Muya, E; Roimen, H (2011)
In Kenya the belowground biodiversity project was implemented in Embu and Taita which are biodiversity hotspots. The objective of the paper is to present and analyze farmers’ knowledge, attitudes and practices at different timelines of the project, as well as identify factors limiting adoption of the best bet technologies. In early 1960’s when natural forest was cleared for farming activities no farm inputs were introduced in food crops until after 10 years. Ever since, to the present similar farm imputs and crops have been propagated continuously leading to declined food production hence the bgbd project interventions. A triangulation of methods, both quantitative and qualitative participatory approaches were used to obtain data from farmers in both benchmark sites. The results showed that most farmers were more aware of bgbd at the end of the project compared to the beginning. As much as the best bet technologies were identified, their adoption was constrained by the unavailability of the technologies in local agro shops. This forced farmers to continue using the farming techniques that had deleterious effects on the soil. Hence farmers adopt what works, but which must be locally available. In this cost considerations did not matter, but simply inaccess.